Tetracycline accelerates the temporally-regulated invasion response in specific isolates of multidrug-resistant Salmonella enterica serovar Typhimurium - Brunelle, Brian W (BioMed Central, 2013)
BACKGROUND: Multidrug-resistant (MDR) Salmonella isolates are associated with increased morbidity compared to antibiotic-sensitive strains and are an important health and safety concern in both humans and animals. Salmonella enterica serovar Typhimurium is a prevalent cause of foodborne disease, and a considerable number of S. Typhimurium isolates from humans and livestock are resistant to three or more antibiotics. The majority of these MDR S. Typhimurium isolates are resistant to tetracycline, a commonly used and clinically and agriculturally relevant antibiotic. Because exposure of drug-resistant bacteria to antibiotics can affect cellular processes associated with virulence, such as invasion, we investigated the effect tetracycline had on the invasiveness of tetracycline-resistant MDR S. Typhimurium isolates. RESULTS: The isolates selected and tested were from two common definitive phage types of S. Typhimurium, DT104 and DT193, and were resistant to tetracycline and at least three other antibiotics. Although Salmonella invasiveness is temporally regulated and normally occurs during late-log growth phase, tetracycline exposure induced the full invasive phenotype in a cell culture assay during early-log growth in several DT193 isolates. No changes in invasiveness due to tetracycline exposure occurred in the DT104 isolates during early-log growth or in any of the isolates during late-log growth. Real-time PCR was used to test expression of the virulence genes hilA, prgH, and invF, and these genes were significantly up-regulated during early-log growth in most isolates due to tetracycline exposure; however, increased virulence gene expression did not always correspond with increased invasion, and therefore was not an accurate indicator of elevated invasiveness. This is the first report to assess DT193 isolates, as well as the early-log growth phase, in response to tetracycline exposure, and it was the combination of both parameters that was necessary to observe the induced invasion phenotype. CONCLUSIONS: In this report, we demonstrate that the invasiveness of MDR S. Typhimurium can be modulated in the presence of tetracycline, and this effect is dependent on growth phase, antibiotic concentration, and strain background. Identifying the conditions necessary to establish an invasive phenotype is important to elucidate the underlying factors associated with increased virulence of MDR Salmonella.